Interactive learning for upgrading and growth: Case of Indonesian fishery firms - Erman Aminullah; Trina Fizzanty; Karlina Sari; Rizka Rahmaida; Qinan Maulana Binu Susanto (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2017)
This paper intends to reveal the interactive learning for upgrading and growth in Indonesian fishery firms. The main question is how learning and innovation have occurred in Indonesian fishery firms. The study was conducted in two categories of fishery firms: fish processing and aquaculture (shrimp). The interfirm interactions contain knowledge flows and feedback in local production network involving local suppliers and foreign buyers. The study found that the model of interactive learning for upgrading and growth work as a coupling of three loops: the upgrading capability, the growth formation, and limiting elements. The upgrading capability is subject to growth formation, which is determined by limiting elements. The limiting elements will control the quantity and quality of materials supply that affect inter-firm interaction. The model suggests that the dynamics of upgrading and growth through interactive leraning will continue in a stable manner by easing the constraints of limiting elements through: combating illegal fishing, encouraging interaction with universities, shifting to higher added value products, institutional support for global trading, preventing shrimp disease, providing infrastructure, business facilities, and regulation information. Key words: upgrading, growth, limiting elements, knowledge flows, production network, global market.